Surface and charge characteristics of selected soils in the tropics - Gallez, A.; Juo, A.S.R.; Herbillon, A. (1976)
Specific surface area and surface charge characteristics of some Alfisols and Ultisols from Nigeria were studied. Specific surface are measured by ethylene glycole retention was generally 2 to 3 times greater than the specific surface area measured by N2 adsorption for both surface and subsoil samples. Soils derived from basalt had the greatest surface area per gram of clay as measured by both methods. The surface charge-pH curves of the soils bear the characteristic features of metallic oxides, indicating that surface charge behaviour of the soils studied follows the constant potential model. Values of PZC for Alfisol and Ultisol samples ranged from pH 3.0 to 3.9. Subsoils generally have higher PZC than corresponding surface horizons. Specific adsorption of sulfate resulted in a shift of the PZC to a higher value and an increase in the magnitude of positive charge. Cation and anion retention measurements showed that soils derived from basement complex rocks and sandstones contain negligible amount of positive charge while soils from basalts bear moderate amount of positive charge at their natural pH condition. Evidence also indicated that the Alfisols and Ultisols bear a small amount of permanent negative charge ranging from 1 to 4 meq/100 g.